EFEK SUBSITUSI PUPUK UREA DENGAN PUPUK BIO SLURRY TERHADAP PRODUKTIVITAS RUMPUT BENGGALA (Panicum maximum cv. Trichoglume) - Witariadi N. M.; N. N. C. Kusumawati (Udayana University, 2019)
This experiment to determine the effect of substitution of urea fertilizer with bio slurry fertilizer on productivity of Panicum maximum cv. Trichoglume grass. The experiment was conducted in a greenhouse for 3 months. The design was used completely randomized design (CRD), with seven treatments and each treatment repeated five times. The treatment was dosage of 200 urea kg/ha (A); 150 kg urea/ha + 10 tons cow bio slurry /ha (B); 100 kg urea/ha + 20 tons cow bio slurry/ha (C); 50 kg urea/ha + 30 tons cow bio slurry/ha (D); 150 kg urea/ha + 10 tons pig bio slurry/ha (E); 100 kg urea/ha + 20 tons pig bio slurry/ha (F); 50 kg urea/ha + 30 tons pig bio slurry/ha (G). Variables observed were plant height, number of tillers, number of branches, number of leaves, leaf dry weight, stem dry weight, total forage dry weight, leaf area per pot, and leaf dry weight ratio with stem dry weight. The results showed that the effectiveness of urea fertilizer substitution with pig bio slurry gave the best growth and production of grass Panicum maximum cv. Trichoglume, where treatment (G) with substitution of 50 kg urea/ha + 30 tons pig bio slurry/ha gave the highest yield. It can be concluded increasng of growth and production of grass Panicum maximum cv. Trichoglume can be substituted with 50 kg urea/ha + 30 tons pig bio slurry/ha. Keywords: substitution, urea, bio slurry, productivity, Panicum maximum